Chalcone-flavone tetramer and biflavones from Aristolochia ridicula - Machado, M. B.; Lopes, LMX (Elsevier B.V., 2005)
Biflavones and a chalcone flavone tetramer were isolated from the leaves of Aristolochia ridicula, together with proto-quercitol. Their structures were determined by spectroscopic methods. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Aristolochia ridicula; Aristolochiaceae; flavonoids; biflavonoid; tetraflavonoid; chalcone-flavone tetramer; cyclitol